PENGARUH CITRA MEREK DAN FASILITAS TERHADAP KEPUTUSAN MINAT PEMBELIAN ULANG DI MASA PANDEMI COVID-19: (Studi Kasus Kedai Kopi Oasis) - Azizah, Rumaisha Nur; Hartono, Budi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Coffee shop businessmen are the group that has had a huge impact during this Covid-19 pandemic. This makes them have to survive by looking for various ways in order to survive without loss and can continue to attract consumers. In the world of entrepreneurship, the main goal is not only how consumers buy their products but how their products are able to continue to compete with competitors and consumers make repeat purchases. One way to survive during this Covid-19 pandemic is to maintain a brand image that is already owned and attached by consumers. Brand image is an important factor that drives consumers to choose the product. Not only by maintaining a brand image, factors such as facilities can also be a factor that needs to be taken into account by coffee shop entrepreneurs because consumer convenience is an important factor. The object in this study is the Oasis Coffee Shop, where the Oasis Coffee Shop is still able to compete during the Covid-19 pandemic with the ability to maintain a brand image on its boba products and the facilities it has provide convenience for its consumers so that it can influence consumers to make repeat purchases. The method used in this research is descriptive qualitative where data collection uses questionnaires and interviews with 30 consumers of the Oasis Coffee Shop. The results of this study indicate that the variable brand image and facilities affect repurchase intention.